2015
DOI: 10.1007/s00787-015-0761-x
|View full text |Cite
|
Sign up to set email alerts
|

Stigma in youth with Tourette’s syndrome: a systematic review and synthesis

Abstract: Tourette's syndrome (TS) is a childhood onset neurodevelopmental disorder, characterised by tics. To our knowledge, no systematic reviews exist which focus on examining the body of literature on stigma in association with children and adolescents with TS. The aim of the article is to provide a review of the existing research on (1) social stigma in relation to children and adolescents with TS, (2) self-stigma and (3) courtesy stigma in family members of youth with TS. Three electronic databases were searched: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 56 publications
2
56
0
Order By: Relevance
“…The wider literature suggests that the complexity of TS extends beyond the physical symptoms. Social adjustment difficulties (Cutler et al 2009), social-and self-stigmatisation (Malli et al 2016;Smith et al 2015), isolation, bullying, peer rejection (Malli and Forrester-Jones 2017;Wadman et al 2013) and poor sense of self-concept due to personalisation of the illness (Hanks et al 2016) are some of the hurdles experienced by children and adolescents affected by TS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wider literature suggests that the complexity of TS extends beyond the physical symptoms. Social adjustment difficulties (Cutler et al 2009), social-and self-stigmatisation (Malli et al 2016;Smith et al 2015), isolation, bullying, peer rejection (Malli and Forrester-Jones 2017;Wadman et al 2013) and poor sense of self-concept due to personalisation of the illness (Hanks et al 2016) are some of the hurdles experienced by children and adolescents affected by TS.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they may face higher difficulties in social relationships (Conelea et al 2013), increased familial/marital stress (Hubka et al 1988), greater propensity for mood and anxiety disturbances (Evans et al 2016), and ultimately a diminished quality of life (QoL) (Conelea et al 2013). There is, however, a scarcity of research exploring the holistic impact of living with TS as an adult, the consequences of the challenges associated with the condition, and how adults with TS view themselves and construct their social and self-identity (Malli et al 2016). By social identity we are referring to the sense of self people derive from their membership in a specific group and the emotional value they attribute to this membership (Tajfel 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Two causes could be considered for the parenting stress in parents of children with tics: the influence of tics themselves and comorbidities. Tics could have a negative impact on family relationships because tics are likely to cause social misperceptions or stigma (14,(48)(49)(50). Parents could become overprotective of, worried about, struggling to accept or trying to control children's tics (14).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of research that demonstrates individuals with Tourette’s experience social difficulties and endure social stigmatisation (Malli et al 2016; Smith et al 2015). A recent systematic review and synthesis indicated that children and adolescents with Tourette’s syndrome report impaired peer relations and are at a significantly higher risk of stigmatisation and victimisation compared to their typically developing peers, including name-calling, relational bullying, teasing, ridicule, discrimination and marginalisation (Malli et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review and synthesis indicated that children and adolescents with Tourette’s syndrome report impaired peer relations and are at a significantly higher risk of stigmatisation and victimisation compared to their typically developing peers, including name-calling, relational bullying, teasing, ridicule, discrimination and marginalisation (Malli et al 2016). …”
Section: Introductionmentioning
confidence: 99%